Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Rolling in the deep: drivers of social preferences and social interactions within a bull shark aggregation in Fiji - Natasha D. Marosi; Samuel Ellis; David M.P. Jacoby; Juerg M. Brunnschweiler; Darren P. Croft (Animal Behaviour, 2026)

Spatiotemporal variability from physics to plankton ecology in an upwelling bay - Monique Messié; Mike McCann; Kathleen J. Pitz; Jacoby D. Baker; John P. Ryan; Steven H.D. Haddock; Francisco P. Chavez (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Rapid Ocean Warming Drives Sexually Divergent Habitat Use in a Threatened Predatory Marine Ectotherm - Lucy R. Mead; Adam Piper; David Jiménez Alvarado; Eva Meyers; Joanna Barker; Hector Toledo‐Padilla; Edy Herraiz; Alberto F. Campoamor; Michael Sealey; Maria Belén Caro; Tomàs Bañeras; Charlotte Pike; et al. (Global Change Biology, 2025)
Climate change poses one of the greatest threats to marine ecosystems worldwide, altering physical, chemical, and biological processes at unprecedented rates. Severe impacts on marine species and habitats have been extensively documented, with shifts in phenology, spatial distribution, and migratory behaviour increasingly pervasive. However, there is a lack of species‐specific data examining responses and adaptation to rapid warming and environmental extremes, especially for marine ectotherms. In this study, we investigate the broad‐scale environmental drivers of distribution in a Critically Endangered ectothermic marine predator, the angelshark Squatina squatina , and report on a behavioural anomaly observed in 2022. Between 2018 and 2023, 112 adult S. squatina were tracked using acoustic telemetry in La Graciosa Marine Reserve in the Canary Islands. Relationships between seasonal presence of S. squatina and remotely sensed environmental parameters were examined with Boosted Regression Tree and Generalised Additive Modelling. Major sex differences were found, with female sharks strongly influenced by environmental conditions and particularly sensitive to temperature, with a possible upper thermal threshold close to 22.5°C. Peak sea surface temperature in the study area increased from 22.99°C to 23.81°C, and the number of days above 22.5°C nearly tripled. Absence of females during the 2022 breeding season coincided with widespread thermal anomalies across the Northeast Atlantic Ocean, with unusually high temperatures persisting later into the year. We conclude that this potentially disrupted seasonal thermal cues for S. squatina movement, leading to sexually divergent habitat use. Given the warming projected for this region, thermal thresholds may increasingly be exceeded, and key areas may become inhospitable for female S. squatina , which is of huge concern for this already highly threatened species. These findings highlight the urgency of identifying species‐specific environmental tolerances and incorporating these into conservation so that management remains ecologically relevant in a rapidly warming ocean.

What acoustic telemetry can and cannot tell us about fish biology - David M. P. Jacoby; Adam T. Piper (Journal of Fish Biology, 2025)
Acoustic telemetry (AT) has become ubiquitous in aquatic monitoring and fish biology, conservation, and management. Since the early use of active ultrasonic tracking that required researchers to follow at a distance their species of interest, the field has diversified considerably, with exciting advances in both hydrophone and transmitter technology. Once a highly specialized methodology, however, AT is fast becoming a generalist tool for those wishing to study or conserve fishes, leading to diversifying application by non‐specialists. With this transition in mind, we evaluate exactly what AT has become useful for, discussing how the technological and analytical advances around AT can address important questions within fish biology. In doing so, we highlight the key ecological and applied research areas where AT continues to reveal crucial new insights and, in particular, when combined with complimentary research approaches. We provide a comprehensive breakdown of the state of the art for applications of AT, discussing the ongoing challenges, where its strengths lie, and how future developments may revolutionize fisheries management, behavioral ecology and species protection. Through selected papers we illustrate specific applications across the broad spectrum of fish biology. By bringing together the recent and future developments in this field under categories designed to broadly capture many aspects of fish biology, we hope to offer a useful guide for the non‐specialist practitioner as they attempt to navigate the dizzying array of considerations and ongoing developments within this diverse toolkit.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

From sneaker to bourgeois male: Long‐term observations on recognized tompot blenny Parablennius gattorugine individuals reveal new information on their biology - Paul Naylor; Teresa Naylor; Louise Hammond; David M. P. Jacoby (Journal of Fish Biology, 2023)
The behaviour of the tompot blenny Parablennius gattorugine was studied by underwater observation and photography on the south‐west coast of the UK over an 11 year period, with >50 individuals identified at two locations by their distinctive skin markings. Observations showed males engaging in rapid swimming behaviour when approached by a female, and younger males using alternative ‘sneaker’ tactics before becoming ‘bourgeois’ territory‐holders. The noninvasive recognition technique also facilitated detailed observations on territory retention (up to 7 years) and agonistic behaviours among both males and females.

The drivers of anguillid eel movement in lentic water bodies: a systematic map - Michael J. Williamson; David M. P. Jacoby; Adam T. Piper (Reviews in Fish Biology and Fisheries, 2023)
Anguillid eels are near globally distributed catadromous fishes with marine spawning areas and inshore and inland growth areas in both lotic (rivers, estuaries) and lentic (lakes, ponds, lagoons) water bodies. As predators, anguillid eels play an important ecological role in both marine and freshwater systems, and several species are harvested commercially for food. However, some of the more widely distributed species have undergone severe declines in recruitment and their population status is now of significant concern. Given the multiple and lengthy migrations undertaken by anguillid eels, understanding of the drivers of movement is fundamental for species conservation and management. Yet, despite the importance of lentic systems to their ecology, most studies on anguillid eel movement have been conducted in lotic systems. Given that key influences on eel migration in lotic water bodies, such as fluctuations in flow and water temperature, may be minimised in lentic environments, the transferability of findings between lotic and lentic systems cannot be assumed. A systematic map was constructed to synthesise current knowledge on the extrinsic and intrinsic drivers of anguillid eel movement in lentic systems. The current state of knowledge of the drivers of eel movement in lentic systems is presented and compared to the relatively well-understood drivers of movement in lotic systems. We also discuss current knowledge gaps and limitations, and identify key future research requirements to inform the management and conservation of anguillid eels in understudied lentic systems. Graphical abstract

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Editorial: Sociality in the Marine Environment - David M. P. Jacoby; Culum Brown; Darren P. Croft; Janet Mann; Johann Mourier (Frontiers in Marine Science, 2022)

Social Network Analysis Reveals the Subtle Impacts of Tourist Provisioning on the Social Behavior of a Generalist Marine Apex Predator - David M. P. Jacoby; Bethany S. Fairbairn; Bryan S. Frazier; Austin J. Gallagher; Michael R. Heithaus; Steven J. Cooke; Neil Hammerschlag (Frontiers in Marine Science, 2021)
Shark dive ecotourism is a lucrative industry in many regions around the globe. In some cases, sharks are provisioned using bait, prompting increased research on how baited dives influence shark behavior and yielding mixed results. Effects on patterns of habitat use and movement seemly vary across species and locations. It is unknown, however, whether wide-ranging, marine apex predators respond to provisioning by changing their patterns of grouping or social behavior. We applied a tiered analytical approach (aggregation-gregariousness-social preferences) examining the impact of provisioning on the putative social behavior of tiger sharks ( Galeocerdo cuvier ) at a dive tourism location in The Bahamas. Using network inference on three years of acoustic tracking data from 48 sharks, we tested for non-random social structure between non-provisioned and provisioned monitoring sites resulting in 12 distinct networks. Generally considered a solitary nomadic predator, we found evidence of sociality in tiger sharks, which varied spatiotemporally. We documented periods of both random ( n = 7 networks) and non-random aggregation ( n = 5 networks). Three of five non-random aggregations were at locations unimpacted by provisioning regardless of season, one occurred at an active provisioning site during the dry season and one at the same receivers during the wet season when provision activity is less prevalent. Aggregations lasted longer and occurred more frequently at provisioning sites, where gregariousness was also more variable. While differences in gregariousness among individuals was generally predictive of non-random network structure, individual site preferences, size and sex were not. Within five social preference networks, constructed using generalized affiliation indices, network density was lower at provisioning sites, indicating lower connectivity at these locations. We found no evidence of size assortment on preferences. Our data suggest that sociality may occur naturally within the Tiger Beach area, perhaps due to the unusually high density of individuals there. This study demonstrates the existence of periodic social behavior, but also considerable variation in association between tiger sharks, which we argue may help to mitigate any long-term impacts of provisioning on this population. Finally, we illustrate the utility of combining telemetry and social network approaches for assessing the impact of human disturbance on wildlife behavior.

Understanding Persistent Non-compliance in a Remote, Large-Scale Marine Protected Area - Claire Collins; Ana Nuno; Annette Broderick; David J. Curnick; Asha de Vos; Thomas Franklin; David M. P. Jacoby; Chris Mees; James Moir-Clark; John Pearce; Tom B. Letessier (Frontiers in Marine Science, 2021)
Area coverage of large-scale marine protected areas (MPAs) (LSMPAs, > 100,000 km 2 ) is rapidly increasing globally. Their effectiveness largely depends on successful detection and management of non-compliance. However, for LSMPAs this can be difficult due to their large size, often remote locations and a lack of understanding of the social drivers of non-compliance. Taking a case-study approach, we review current knowledge of illegal fishing within the British Indian Ocean Territory (BIOT) LSMPA. Data stemming from enforcement reports (2010–20), and from fieldwork in fishing communities (2018–19) were combined to explore and characterise drivers of non-compliance. Enforcement data included vessel investigation reports ( n = 188), transcripts of arrests (20) and catch seizures (58). Fieldwork data included fisher interviews (95) and focus groups (12), conducted in two communities in Sri Lanka previously associated with non-compliance in BIOT LSMPA. From 2010 to 2020, there were 126 vessels suspected of non-compliance, 76% of which were Sri Lankan. The majority of non-compliant vessels targeted sharks (97%), catching an estimated 14,340 individuals during the study period. Sri Lankan vessels were primarily registered to one district (77%) and 85% operated from just two ports within the fieldwork sites. Social Network Analysis (SNA) showed that 66% of non-compliant vessels were linked by social ties, including sharing crew members, compared with only 34% of compliant vessels. Thematic analysis of qualitative data suggested that perceptions of higher populations of sharks and social ties between vessels may both be important drivers. We discuss our findings within a global context to identify potential solutions for LSMPA management.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Satellite Remote Sensing in Shark and Ray Ecology, Conservation and Management - Michael J. Williamson; Emma J. Tebbs; Terence P. Dawson; David M. P. Jacoby (Frontiers in Marine Science, 2019)

An eye in the sky reveals the collective dynamics of free‐ranging shark aggregations - David M. P. Jacoby (Journal of Fish Biology, 2019)

Applicability of time-of-flight-based ground and multispectral aerial imaging for grapevine canopy vigour monitoring under direct root-zone deficit irrigation - Carlos Zúñiga Espinoza; Anura P. Rathnayake; Momtanu Chakraborty; Sindhuja Sankaran; Pete Jacoby; Lav R. Khot (International Journal of Remote Sensing, 2018)

Territoriality in the tompot blenny Parablennius gattorugine from photographic records - P. Naylor; D. M. P. Jacoby (Journal of Fish Biology, 2016)
The behaviour of the tompot blenny Parablennius gattorugine was studied from a long‐term underwater photographic record from two sites on the south‐west coast of the U.K. Repeated observations of individually identifiable P. gattorugine during 112 dives revealed that male P. gattorugine may guard eggs in a particular crevice over subsequent breeding seasons, reside in the same location for up to 4 years and recover from injuries received in disputes over territory. Further observations included resident males wiping eggs with greatly expanded anal glands, adult‐type fighting between juveniles and unusual behaviour where a large male manipulated an empty mollusc shell for the attention of two smaller conspecifics.

Reproductive biology of invasive lionfish (Pterois spp.) - Patrick G. Gardner; Thomas K. Frazer; Charles A. Jacoby; Roy P. E. Yanong (Frontiers in Marine Science, 2015)

Shark personalities? Repeatability of social network traits in a widely distributed predatory fish - David M. P. Jacoby; Lauren N. Fear; David W. Sims; Darren P. Croft (Behavioral Ecology and Sociobiology, 2014)

Simultaneous quantification of 12 different nucleotides and nucleosides released from renal epithelium and in human urine samples using ion-pair reversed-phase HPLC - Alberto Contreras-Sanz; Toby S. Scott-Ward; Hardyal S. Gill; Jennifer C. Jacoby; Rebecca E. Birch; James Malone-Lee; Kevin M. G. Taylor; Claire M. Peppiatt-Wildman; Scott S. P. Wildman (Purinergic Signalling, 2012)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

Social behaviour in sharks and rays: analysis, patterns and implications for conservation - David M P Jacoby; Darren P Croft; David W Sims (Fish and Fisheries, 2012)
There are widespread records of grouping behaviour in both adult and juvenile sharks and rays (Class Chondrichthyes, Subclass Elasmobranchii). Yet despite burgeoning descriptions of these events, many of the proximate and ultimate causes of group living in these top predators remain elusive. Given the documented negative anthropogenic effects on many shark populations globally, there is an increasing need to understand how behaviourally mediated grouping influences population distributions and abundance, and the role this plays in exacerbating vulnerability to fishing mortality. Here, we analyse group living in elasmobranchs: we describe our current understanding of the patterns, mechanisms and functions of both aggregation (where grouping is not driven by social mechanisms) and social grouping (where grouping is influenced by social interaction) and discuss some of the current methods used to study social behaviour in this taxa. In particular, social preferences in elasmobranchs have received relatively little attention. We propose that the study of shark aggregations may benefit from a more fine‐scale analytical approach offered by detailed exploration of social interactions using social network analysis. Better understanding of the frequency and longevity of social relations, in conjunction with current long‐term data on habitat use and site philopatry, will likely serve for a more informed approach to coastal and pelagic elasmobranch conservation initiatives.

The effect of familiarity on aggregation and social behaviour in juvenile small spotted catsharks Scyliorhinus canicula - D. M. P. Jacoby; D. W. Sims; D. P. Croft (Journal of Fish Biology, 2012)
This study was designed to address whether juvenile small spotted catsharks Scyliorhinus canicula aggregate and to determine whether potential aggregation is underpinned by social preferences for conspecifics. Using controlled and replicated experiments, the role of familiarity as a potential mechanism driving aggregation and social behaviour in this species was considered. Observed S. canicula association data compared to null model simulations of random distributions revealed differences in aggregation under different social contexts. Only familiar juvenile S. canicula aggregated more than would be expected from random distribution across their habitat. Familiarity increased the mean number of groups but did not significantly affect mean group size. Significant preference and avoidance behaviour across all groups were also observed. Furthermore, the strength of social attraction, quantified by the mean association index, was significantly higher in groups containing familiar individuals. Mixed familiar and unfamiliar treatments were also conducted to test for within‐ and between‐group effects, finding high variation across replicates with some groups assorting by familiarity and others not. It is believed that this study is the first to examine experimentally the influence of conspecific familiarity on aggregation behaviour in sharks. These results not only imply a functional benefit to aggregation, but also suggest that persistent social affiliation is likely to influence dispersal following hatching in this small benthic elasmobranch.

Analysis of climate policy targets under uncertainty - Mort Webster; Andrei P. Sokolov; John M. Reilly; Chris E. Forest; Sergey Paltsev; Adam Schlosser; Chien Wang; David Kicklighter; Marcus Sarofim; Jerry Melillo; Ronald G. Prinn; Henry D. Jacoby (Climatic Change, 2012)

Lrg1p functions as a putative GTPase-activating protein in the Pkc1p-mediated cell integrity pathway in Saccharomyces cerevisiae - A. Lorberg; H.-P. Schmitz; J. Jacoby; J. Heinisch (Molecular Genetics and Genomics, 2001)

The PH domain of the yeast GEF Rom2p serves an essential function in vivo - A. Lorberg; J. Jacoby; H.-P. Schmitz; J. Heinisch (Molecular Genetics and Genomics, 2001)

Integrated Global System Model for Climate Policy Assessment: Feedbacks and Sensitivity Studies - R. Prinn; H. Jacoby; A. Sokolov; C. Wang; X. Xiao; Z. Yang; R. Eckhaus; P. Stone; D. Ellerman; J. Melillo; J. Fitzmaurice; D. Kicklighter; et al. (Climatic Change, 1999)

Growth, cold-hardiness, protein content, and digestibility of 70 Leucaena seedlots on three sites in Texas, USA - P. Felker; C.T. Sorensson; D. Ueckert; P. Jacoby; E. Singer; R. Ohm (Agroforestry Systems, 1998)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

Mousepox in inbred mice innately resistant or susceptible to lethal infection with ectromelia virus V. Genetics of resistance to the Moscow strain - D. Brownstein; P. N. Bhatt; R. O. Jacoby (Archives of Virology, 1989)

Evidence that NK cells and interferon are required for genetic resistance to lethal infection with ectromelia virus - R. O. Jacoby; P. N. Bhatt; D. G. Brownstein (Archives of Virology, 1989)

Mousepox in inbred mice innately resistant or susceptible to lethal infection with ectromelia virus. IV. Studies with the Moscow strain - P. N. Bhatt; R. O. Jacoby; Lisa Gras (Archives of Virology, 1988)

The pathogenesis of rat virus infection in infant and juvenile rats after oronasal inoculation - R. O. Jacoby; P. N. Bhatt; Diane J. Gaertner; Abigail L. Smith; Elizabeth A. Johnson (Archives of Virology, 1987)

Persistence of rat virus in seropositive rats as detected by explant culture - F. X. Paturzo; R. O. Jacoby; P. N. Bhatt; Abigail L. Smith; Diane J. Gaertner; R. B. Ardito (Archives of Virology, 1987)

Genetic resistance to lethal flaviviral encephalitis - P. N. Bhatt; Elizabeth A. Johnson; Abigail L. Smith; R. O. Jacoby (Archives of Virology, 1981)

Experimental infection of adult axenic rats with Parker's Rat Coronavirus - P. N. Bhatt; R. O. Jacoby (Archives of Virology, 1977)